Elementary School Flipped Learning STEM Education as a Medium for Engaging and Innovative Learning - Maspul, Kurniawan Arif (Jurnal Pendidikan LLDIKTI Wilayah 1 (JUDIK), 2023)
In today's quickly changing world, it is critical to provide students with the skills and information needed to flourish in STEM disciplines. Flipped learning, an innovative educational strategy, has gained appeal as a means to increase student engagement and deepen comprehension of STEM disciplines. This article provides a thorough examination of flipped learning in primary school STEM teaching, supported by relevant theories and literature. Flipped learning flips the traditional classroom approach by delivering instructional information outside of class, freeing up in-class time for active learning, hands-on activities, and collaborative problem-solving. The Cognitive Load Theory provides a theoretical underpinning for flipped learning by reducing cognitive load and allowing students to actively interact with difficult STEM subjects. Flipped learning boosts student motivation, critical thinking abilities, and information acquisition in STEM courses, according to research. This study confirms the positive impact of flipped learning on student engagement, critical thinking abilities, and enthusiasm for STEM disciplines in elementary school using a comprehensive methodology that includes literature analysis, classroom observations, and interactions with educators and students. Flipped learning is emerging as a valuable tool for preparing students with the skills they need to excel in STEM professions, encouraging additional investigation and collaboration among educators.